Review paper: potential benefits of Pet-Facilitated-Therapy (PFT) in children with Autism Spectrum Disorder (ASD) - Cho Cho Zaw, Cho Cho Zaw (2017)
Autism Spectrum Disorder (ASD) is a wide range of social, mental, and developmental disorder seen among the young children. It is commonly used to describe individuals who have autism or autistic type features. And it is mentioned as a spectrum since different individuals with autism shows different symptoms rather than one single disorder. However, they have some basic features to mention them generally as having autism such as deficits in social interaction, communication and the presence of restricted or repetitive behaviors. Autism seems to be related with genetic, non-genetic or environmental factors. Since the causes of ASD are not clear, the specific treatment of it are still lacking. Alternative and complementary therapies such as diet, exercise, medications, acupuncture are utilized for improving the conditions of the children with ASD. Pet facilitated therapy (PFT) has been increasingly popular in recent years and it is counted as one form of alternative therapies in human medical field in some countries. The purpose of this study is to examine the potential benefits of PFT that would offer to the children with ASD. The findings revealed that pet therapy is considered as highly beneficial and recommended as one of the alternative therapies. The findings are categorized into different themes such as potential benefits of PFT in physical movement; communication, social and language skills; improving positive behaviors and reducing negative behaviors; and stress in children with ASD. This study is hoped to give insight to public, health care professions so that they can make use of PFT in providing effective care to the children with ASD.